The Effect of Topical 0.1% Pomegranate Extract (Punica Granatum) on Trans Epidermal Water Loss (Tewl) and Skin Ph Levels in Patients with a History of Atopic Dermatitis - Fernandes, Albert; Widayati, Retno Indar; Riyanto, Puguh (Syntax Corporation Indonesia, 2024)
Repairing the skin barrier with moisturizers is one of the five main pillars of treating atopic dermatitis. Petrolatum is considered the gold standard, but its consistency is too thick and oily making it less comfortable to use. Moisturizers containing pomegranate extract (Punica granatum) can be an alternative choice that is more comfortable to use. The effectiveness of this pomegranate extract can be eval__uated using TEWL and pH examinations which are considered accurate indicators for changes in skin barrier conditions. Effectiveness of topical administration of 0.1% pomegranate extract in reducing TEWL and skin pH in sufferers with a history of AD.Single blind randomized clinical trial with two parallel group pre and post design. 34 sufferers with a history of AD were randomly divided into treatment groups (topical 0.1% pomegranate extract, 17 subjects) and control group (topical 100% petrolatum, 17 subjects). Moisturizer was applied twice daily to the volar area of ​​the forearm for 4 weeks. Both groups showed a significant decrease in TEWL after 4 weeks with a TEWL delta of -5.2±2.31g/m2/hour (p<0.001) in the pomegranate extract group and-7.0±7.95g/m2/hour(p=0.003) in the petrolatum group. There was no significant difference in TEWL reduction between the two study groups.The pomegranate extract group showed a significant decrease in pH after 4 weeks with a pH delta of -0.5±0.10(p<0.001), while the petrolatum group actually showed a slight increase with a pH delta of0.0±0.59 (p=0.6). The pomegranate extract group showed a significantly greater decrease in pH (p<0.001).Topical 0.1% pomegranate extract is as effective as 100% petrolatum in reducing TEWL, but more effective in lowering skin pH.